PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO PEMBELAJARAN PADA MATA PELAJARAN IPA DALAM IMPLEMENTASI KURIKULUM 2013 (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
AbstractThe learning process plays an important role in producing the quality of graduates. The mainthing that must be considered by education stakeholders is to create quality learning. Manyaspects can affect the quality of education, including: qualified and qualified teachers withqualifications mandated by teacher and lecturer laws, use of interesting and varied teachingmethods, positive learners' learning behaviors, learning conditions and atmosphere which isconducive to learning and the use of appropriate learning tools to support the learning process.Student achievement data of SMP Negeri 1 Pulau Sembilan Year Lesson 2016/2017 on sciencesubjects from subject Teachers found that 42% of students have enough value, 33% studentshave good grades and 25% of students have very good grades. The results of the interview to thestudents that 70% of students feel constrained when understanding the material, while 95% ofstudents want the teaching-learning materials that can support the understanding of sciencematerials. The purpose of research and development are: (1) developing teaching-learningmaterials based on learning videos on science subjects, (2) students' learning outcomes afterlearning process using instructional materials based on learning videos on science subjects.Research and development methods used Research and Development (R & D). Development iscarried out with reference to the ADDIE (Analyze, Design, Development, Implementation,Evaluation) model proposed by Russell and Molenda. The validation of instructional materialsbased on learning videos on these subjects is assessed on the feasibility of content, presentation,and language by expert, teacher, and peer review validation. Based on the validation of thecontent feasibility, presentation, and instructional materials based on learning videos on sciencesubjects, it is considered feasible to be used and implemented in SMP Negeri 1 Pulau SembilanKotabaru Regency. Student learning outcomes were analyzed by parametric test using wilcoxontest which was processed using IBM SPSS Statistic 22 software. The result of research anddevelopment were (1) instructional material based on learning video on science subjectsdeveloped using ADDIE model include Analyze, Design, Development, Implementation, andEvaluation, (2) student learning outcomes after following the learning process usinginstructional materials based on learning video on science subjects experience a significantimprovement. Increased student learning outcomes seen from the p-value of -4.462 below(